TILLING mutants of durum wheat result in a high amylose phenotype and provide information on alternative splicing mechanisms - Sestili, Francesco (Plant science : an international journal of experimental plant biology, 2015)
Copyright © 2015 Elsevier Ireland Ltd. All rights reserved.